Tribute to Julio Ísmodes Alegría - Palacios, Leoncio (2017)
On June 11, 2017, Professor Julio Ísmodes, remembered member of the Fifth Promotion of the former UNI School of Economics, passed away. Determined to become a professional, he overcame economic hardship by sharing his university studies with part-time work at the Jockey Club del Perú.One of his most cherished personal goals -and to which he dedicated the last years of his academic life- was the preparation of his doctoral thesis on the urban economy of Lima. His departure occurred when he was on the verge of realizing his most cherished dream.